(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The expansion of human civilization and culture around the world has resulted in many shifts. Technology is always advancing and becoming more sophisticated so that it can help solve problems like these. Today, a large number of people are employed in a single location, and the task is accomplished efficiently with the assistance of management and technology. The term “management” can relate to the managing of humans or goods. On the other hand, the administration of a company’s people resources is referred to as “human resource management” (HRM), which is an abbreviation. The ability to provide HRM services is exclusive to large corporations that already own qualified staff, advanced technology, and established communication channels.